English Textbooks for Teaching and Learning English as a Foreign Language: Do They Really Help to Develop Communicative Competence? - Luis Fernando Gómez-Rodríguez (Universidad de La Sabana, 2010)
Communicative texts are educational materials for language learning that focus on the genuine use of a language for communicative purposes in a variety of meaningful contexts. Above and beyond the mere study of linguistic forms, these texts offer opportunities to communicate, interact and negotiate meaning. Three common types of English language practice are analyzed in this article: mechanical practice, meaningful practice and communicative practice. Five English texts representative of those currently used in Colombia were selected to determine to what degree they include genuine communicative tasks and, in this respect, how they encourage the development of communicative competence. The extent of communicative practice these texts offer students of English was found to be less than the amount of mechanical and meaningful practice. This information should be useful for training English teachers, particularly those who generally focus their classroom activity on the use of texts. Methodological suggestions are offered, based on the results of the study.